HeadSmart – be brain tumour aware (HeadSmart): has it made a difference to professional awareness and knowledge of brain tumours?. (24th May 2012) - Liu, JF; Wilne, S; Clough, L; Dudley, J; Lakhanpaul, M; Kennedy, C; Grundy, RG; Baker, M; Trusler, J; Carbury, P; Lindsell, S; Walker, DA
Abstract : Aims: To determine the impact of the HeadSmart Campaign upon professional awareness of childhood brain tumours. Introduction: The HeadSmart national awareness campaign (www.headsmart.org.uk ) aims to disseminate the RCPCH endorsed Brain Pathways Guideline for brain scanning of patients with symptoms suggestive of brain tumour. The campaign aims to reduce median symptom interval for childhood brain tumours to 5 weeks in the UK. Methods: An on-line survey was distributed through paediatrics, emergency medicine and general practice networks pre (spring 2011) and post (on going, opened Nov 2011) the campaign launch in June 2011. Results: 325 (Pre) / 164 (Post) responses were received. Responders included 28% / 54% consultants, 24% / 20% ST4-7, 25% / 6.1% general practitioners. Comparison of pre / post responses showed professionals recognised the risk of visual loss (94% / 97%), cognitive deficits (98% / 96%) and endocrinopathies (88% / 92%) associated with delays in diagnosis. At least 85% / 94% identified headache, vomiting, visual abnormalities, abnormal coordination, disturbed puberty, lethargy and irritability as indicators of brain tumour, 79% / 82% recognised weight loss and 76% / 94% recognised abnormal head position, 78% / 75 % knew that children with brain tumours have multiple symptoms and signs by diagnosis. 27% / 50 % felt confident in their ability to recognise a case of brain tumour. In the post survey 69.2% had become aware of the HeadSmart campaign from College communications (68%), national or regional meetings (28%), personal discussion with colleague (26%), posters or information packs at workplace (24%) and from training sessions (20 %). Of the HeadSmart campaign materials, 43% had seen or used the symptom card, 43% the quick reference guide, 41% the campaign leaflet and 22% the website. Healthcare professionals felt that the symptom card and the quick reference guide were the most useful campaign materials. Conclusions: Healthcare professionals' awareness and knowledge of symptoms and signs justifying scanning for brain tumour were enhanced following launch of the HeadSmart campaign. 69% of healthcare professionals were aware of the HeadSmart campaign messages. The campaign will continue until 2013 aiming to reach 100% of these professional groups.